Chinese historical microdemography - Harrell, Stevan (University of California Press, 1995)
Using local studies to answer global questions, this compilation challenges traditional notions concerning historical Chinese population trends. Genealogies, epitaphs, and household registers are some of the local and primary materials used to examine the important issues of fertility, mortality, family structure, and migration patterns.
Papers from the conference sponsored by the Joint Committee on Chinese Studies.
Keywords: China -- Population.; Families -- China -- History.; Marriage -- China.; China -- Social conditions -- 1644-1912.; Social history.; Familles -- Chine -- Histoire.; Mariage -- Chine.; Chine -- Conditions sociales -- 1644-1912.; Histoire sociale.; social history.; SOCIAL SCIENCE -- Demography.; SOCIAL SCIENCE / Demography; Families; Marriage; Population; Social conditions; China; Bevolking.; China.; 1644-1912; Demography; dissertations.; History; Geschiedenis (vorm); Academic theses.; Thèses et écrits académiques.